Akar Sejarah Pemikiran al-ShÃ¢tibÃ® tentang Rukhsah - SyarÃ¢Â€Â™i, Makmun (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
Al-Shatibi is known in the history of Islam as a prioner in the theory of Syariâah. He wrote al-Muwafaqat, his magnum opus. This paper deals with this historic figure by referring to his theory concerning rukhsah; an exemption given to Muslim in performing the rites for certain and acceptable reason. The paper will look at this concept by considering the background in which it is propounded. We believe that his theory is not conceptualised out of the blue. Two key words will be used to embark on this task, namely âadamu al-Haraj and (tatbîq). The former is about the removing the difficulty from man, and the latter is about the application of the Syariâah in the live of individual. By using the first concept, the paper will try to reconstruct the fact that in propounding his theory of rukhsan, al-Syatibi always keeps in mind the fact that Islam is revealed mainly to make life easy, and not vice versa. By using the second concept in the meantime, we try to show that the Syariâah lawsârukhsah includedâare revealed to apply (the application Syariâah is not always in political context).